Influence of extended pi-conjugation units on carrier mobilities in conducting polymers - Harima, Yutaka; Kim, D. H.; Tsutitori, Y.; Jiang, Xiaoqing; Patil, R.; Ooyama, Y.; Ohshita, J.; Kunai, A. (Chemical Physics Letters, 2006)
Carrier mobilities in thin films of copolymers with repeat units consisting of oligothiophenes bridged by Si atoms are measured over a range of doping levels, where the numbers of thienylenes in the repeat unit are 7, 8, 10, 12, and 14. The mobilities for these polymer films increased with the increase in doping level and the mobility enhancement followed an increasing order of the pi-conjugation length. The magnitude of the mobility increase for the Si polymer comprising 14 thiophene units reached ca. 10(4), implying that this pi-conjugation length is almost sufficient to reproduce transport properties of polythiophenes. (c) 2006 Elsevier B.V. All rights reserved.

Correlation between mobility enhancement and conformational change in polyaniline and its derivatives: polaron lattice formation - Harima, Yutaka; Ogawa, Fumiyuki; Patil, Rahul; Jiang, Xiaoqing (Electrochimica Acta, 2007)
Conformational changes in polyaniline, poly(methyl aniline), and poly(methoxyaniline) are studied in perchloric acid and acetonitrile by means of an in situ reflection technique with oxidation level as a parameter. Stretching of polymer chains leading to enhancement of specular reflection at the polymer-coated electrodes is found to be well correlated with the increase in carrier mobility. The concomitant change in mobility and chain conformation observed with the polyaniline family is explained in terms of the formation of polaron lattice at increased oxidation levels. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Conformation; polyaniline; reflection; scattering : mobility

Influence of film structure on mobilities of charge carriers in conducting polymers - Harima, Yutaka; Jiang, Xiaoqing; Patil, Rahul; Komaguchi, Kenji; Mizota, Haruo (Electrochimica Acta, 2007)
Two sorts of poly(3-hexylthiophene) (PHT) films with the same chemical compositions were prepared, and their electrochemical, spectroscopic, and transport properties were studied with a special interest in a possible influence of film structure on mobilities of charge carriers. One of the PHT films was electrochemically synthesized using 3-hexylthiophene as a monomer (as-grown film) and the other was obtained by dissolving the as-grown film in chloroform and then casting the polymer solution (cast film). A clear difference was observed in the mobility versus doping level plot between the two sorts of PHT films, demonstrating that the difference is caused only by a distinction in film structure. An initial decreasing feature of the mobility plot observed for the cast films was accounted for in terms of swelling of the films at an early stage of doping. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Doping; electrosynthesis; mobility; poly(3-hexylthiophene); swelling

New technique to study kinetics of chain conformation in polyaniline films - Harima, Yutaka; Kishimoto, Kazuya; Ogawa, Fumiyuki; Jiang, Xiaoqing; Patil, Rahul (Polymer Journal, 2007)
Keywords: Conformation; kinetics; laser; polyaniline; reflection

Transport study on as-grown and cast films of electrogenerated poly(3-hexylthiophene) - Jiang, Xiaoqing; Harima, Yutaka; Patil, Rahul (Materials Letter, 2007)
Two kinds of poly(3-hexylthiophene) films with identical chemical compositions are prepared. One of the films is obtained by electropolymerization of 3-hexylthiophene (as-grown film) and the other is prepared by casting a solution dissolving the as-grown film (cast film). A clear difference is found in the mobility vs. doping level plots between the as-grown and cast films and its reason is discussed. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: mobility; poly(3-hexylthiophene); swelling; thin film; transport mechanism